Turning training into learning : how to design and deliver programs that get results - Furjanic, Sheila W.; Trotman, Laurie A. (New York : AMACOM, 2000)
This book is about: The training process: creating the foundation; The Learn process: linking training to learning; ...
Keywords: Training; Employees; Employees -- Training of